Empirical study of stirring conditions on emulating rayleigh fading channels in a reverberation chamber. Issue 7 (July 2017) - Nguyen, Tien Manh; Kwon, Jong Hwa; Chung, Jae‐Young
Abstract: An empirical study was performed to understand the relationship of stirring conditions on emulating Rayleigh fading channel inside of a reverberation chamber. The latter has dimensions of 1.8 m × 2.4 m × 1.6 m and equipped with 3 stirrers for rapid over‐the‐air testing of mobile communication devices. The stirrers were selectively turned on and off, and then the generated Rayleigh fading channel was compared with the ideal one by calculating the mean‐squared error. The results indicate that the Rayleigh fading channel inside the chamber is mostly affected by the stirrer close to the transmitting antenna. It was also demonstrated that turning on all the 3 stirrers further reduces the build‐up time of a Rayleigh fading channel, resulting in faster over‐the‐air testing capability.